Pengaruh Kepemimpinan Kepala Sekolah Dan Komitmen Guru Terhadap Kinerja Guru: Studi Pada Guru SMPN I Arosbaya Kabupaten Bangkalan - Dian Hikmawaty; Nugroho Mardi; Chamariyah Chamariyah (Journal of Management and Creative Business, 2024)
Dian Hikmawaty, 2023. The Influence of Principal Leadership and Teacher Commitment on Teacher Performance (Study of Teachers at SMPN I Arosbaya, Bangkalan Regency). This type of research is explanatory research, the approach used is a quantitative approach, the research sample is 45 people. The analysis tool uses Smart PLS (Partial Least Square). Research objectives: 1). To test and analyze the direct influence of the principal's leadership on the performance of teachers at SMPN I Arosbaya, Bangkalan Regency. 2). To test and analyze the direct influence of teacher commitment on teacher performance at SMPN I Arosbaya, Bangkalan Regency. 3) To test and analyze the indirect influence of the principal's leadership on the performance of teachers at SMPN I Arosbaya, Bangkalan Regency. 4) To test and analyze the indirect influence of teacher commitment on the performance of teachers at SMPN I Arosbaya, Bangkalan Regency. The research results show that: 1) The principal's leadership has a positive and insignificant effect on teacher performance with an original sample value of 0.113. 2) Teacher commitment has a significant positive effect on teacher performance with an original sample value of 0.477. 3) The principal's leadership has a significant positive effect on teacher performance with an original sample value of 0.099. 4) Teacher commitment has a significant positive effect on teacher performance with an original sample value of 0.252.